A review: Influence of processing techniques on nutritional composition and antinutritional components of corn (Zea mays L.) kernels / Nur Syazana Shahabuddin and Marina Zulkifli - Shahabuddin, Nur Syazana; Zulkifli, Marina (2021)
Corn (Zea mays L.) has been widely cultivated in Malaysia and it is the most prevalent cereal grains crop globally. The majority of essential nutrients can be found in the kernel parts of the corn which are edible and industrially processed to produce various kinds of food products. However, the presence of antinutritional components in the corn kernels is worrying as they can block the absorption of nutrients. Therefore, this paper aimed to review the processing techniques available in lowering the deleterious effects caused by consuming the antinutritional components such as saponin, tannin, and phytate. Boiling, roasting, fermentation, and germination are the processing techniques being studied. The findings revealed that all processing techniques done on yellow corn kernels caused reductions in the level of antinutritional components as compared to the raw corn kernels. Roasting and germination have the utmost reduction in the level of antinutritional components followed by fermentation, and boiling. Additionally, the processing techniques in enhancing the nutritional compositions are positively proven as it is believed to increase the kernels’ protein digestibility, enhance the mineral extractability, and extend the shelf life of the product. Despite consuming antinutrient is reported to be risky, taking them at low concentrations may favourably give positive effects on human health. Obtained results suggested that processed corn kernels could be used in the food industry before processing them into end products. For that reason, more comprehensive research should be carried out in the future to explore the variety of other corn species, especially pigmented corn.